Mechanistic study of the formation of multiblock π-conjugated metallopolymer - Peverari, Camila R. [UNESP]; David-Parra, Diego N.; Barsan, Madalina M.; Teixeira, Marcos F.S. [UNESP] (Elsevier, 2016)
Electropolymerization of a π-conjugated polymer from [N,N′-bis(salicylidene)-o-phenylenediamine]nickel(II) complex ([Ni(salophen)]) on the surface of indium-tin-oxide (ITO) was studied. Two structures of the polymer have been proposed based on the theorem of molecular columns. The highlighted structures are the molecular column of the central aromatic rings (MCCAR) and molecular column of the side aromatic rings (MCSAR). The molecular structures were obtained by control of the potential scan rate in the electropolymerization step. The MCCAR structures are stable and structurally compact, whereas the MCSAR structures are less compact. Electrochemical measurements, atomic force microscopy (AFM), UV–Vis spectroscopy, FTIR Raman spectroscopy and optical microscopy support the formation of the multiblock π-conjugated polymer.
Keywords: Electropolymerization; Metallopolymer; Molecular columns; Molecular conductivity; π-Conjugated polymer